State fragility, displacement and development interventions - Araya, Y (Refugee Studies Centre, University of Oxford, 2013)
The development approach to displacement brings advantages not only in addressing the needs of refugees, IDPs and host communities but also in helping societies tackle the underlying aspects of fragility that may have caused the displacement.